Міжнародні трудові стандарти у сфері робочого часу та стан їх імплементації в Україні - Іваницький, А. (Київський національний університет імені Тараса Шевченка, 2019)
Проаналізовано систему міжнародно-правового регулювання робочого часу, яка є складною впорядкованою су купністю міжнародних договорів, законодавства ЄС і практики ЄСПЛ, що закріплюють основоположні принципи та міжнародні трудові стандарти у сфері робочого часу. Наведено класифікацію джерел міжнародно-правового регу лювання робочого часу: 1) міжнародні договори; 2) законодавчі акти ЄС; 3) практика ЄСПЛ. Оскільки найбільшу час тину джерел міжнародно-правового регулювання робочого часу становлять міжнародні договори, то запропоно вано класифікувати їх залежно від суб'єктів, у рамках діяльності яких укладаються такі договори: 1) договори в рамках діяльності ООН; 2) договори в рамках діяльності Ради Європи; 3) договори в рамках діяльності МОП; 4) договори в рамках діяльності ЄС. Досліджено положення міжнародно-правових актів щодо робочого часу, звертається увага на їхні особливості. Надано рекомендації щодо подальшої імплементації положень Директиви № 2003/88/ЄС "Про деякі аспекти організації робочого часу" у національне трудове законодавство.

The purpose of this article is to clarify the system and a thorough analysis of the sources of international legal regulation of working time. During the study a number of methods have been used, namely: the formal-logical method has been used for the classification of sources of international legal regulation of working time and relevant international agreements; the system-structural method and the synthesis method – for the analysis of the provisions of the EU Directive 2003/88/EC on certain aspects of the organization of working time, as well as the formal-dogmatic and modeling method – for providing recommendations on the harmonization of national legislation with to the relevant Directive. This study analyzes the system of international legal regulation of working time, which is a complex orderly set of international treaties, EU legislation and ECHR practices that underpin fundamental principles and international labour standards in the field of working time. The scientific work presents the classification of sources of international legal regulation of working time for: 1) international agreements; 2) EU legislation; 3) ECHR practice. Since most of the sources of international legal regulation of working time are international treaties, it is proposed to classify them according to the entities within which the following treaties are concluded: 1) treaties within the UN; 2) treaties within the Council of Europe; 3) treaties within the ILO; 4) treaties within the EU. ILO treaties are proven to be crucial in the area of international legal regulation of working time, as the ILO is an international organization, a specialized UN agency, established to support international cooperation in peacekeeping around the world and to reduce social injustice at the expense of improving working conditions. First of all, for the qualitative perception of the provisions relating to international legal regulation of working time, it is necessary to define the concept of "international labour standards", which is applied in the framework of the ILO activities. International labour standards are legal instruments developed by the ILO (taking into account the principle of tripartite representation – governments, workers and employers) that set out the fundamental principles and rights in the field of labour. The main forms of consolidation of such standards are ILO conventions and recommendations. The provisions of sources of international legal regulation of working time are studied, attention is paid to their peculiarities and specificity. A number of recommendations have been made to further implement the provisions of Directive 2003/88/EC on certain aspects of the organization of working time in national labour law. In particular, it is established that this Directive establishes minimum safety and health requirements for the organization of working time and applies to: minimum periods of daily rest, weekly rest and annual leave, as well as breaks and maximum weekly working hours; some aspects of night work, shift work and work arrangements.
International Labor Standards and Their Implementation in Ukraine
Keywords: міжнародні стандарти праці; конвенція МОП; директива ЄС; адаптація законодавства; Міжнародна організація праці; Угода про асоціацію; international labor standards; ILO convention; EU directive; approximation of laws; International Labor Organization; Association Agreement